Genetic Manipulation of M13 Bacteriophage for Enhancing the Efficiency of Virus‐Inoculated Perovskite Solar Cells with a Certified Efficiency of 22.3% (Adv. Energy Mater. 38/2021). Issue 38 (14th October 2021) - Han, Jiye; Kim, Kyusun; Nam, Jeong‐Seok; Hong, Sung Jun; Choi, Eun Jung; Kim, Dawoon; Chung, In; Lin, Hao‐Sheng; Kim, Tae‐Dong; Strano, Michael S.; Han, Byungchan; Oh, Jin‐Woo; et al.
Abstract : Virus‐Inoculated Perovskites In article number 2101221, Jin‐Woo Oh, Hyung Do Kim, Il Jeon, and co‐workers report genetic modification of M13 bacteriophages to amplify amino acid K, which functions as a perovskite growth template and a stronger passivator than the wild‐type virus in PSCs. The modified virus‐added perovskite solar cells exhibited a higher efficiency of 23.6% than the wild‐type counterparts (22.8%). The observed enhancement is attributed to slightly larger perovskite grains and strong grain boundary passivation. The obtained device efficiency has been certified by the national research center.